2021
DOI: 10.1021/acsmaterialslett.1c00673
|View full text |Cite
|
Sign up to set email alerts
|

MXene─A New Paradigm Toward Artificial Nitrogen Fixation for Sustainable Ammonia Generation: Synthesis, Properties, and Future Outlook

Abstract: Ammonia is a commodity chemical that is manufactured worldwide and supports a growing population. Industrially, ammonia synthesis is dominated by the energy-intensive Haber−Bosch process, thus necessitating the development of a greener approach. Recently, two-dimensional transition-metal carbides/nitrides/carbonitrides, MXenes are emerging as optimistic prospects for the environmentally benign electro-and photocatalytic nitrogen fixation to ammonia. MXenes exhibit excellent hydrophilicity, large specific surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 224 publications
(525 reference statements)
0
9
0
Order By: Relevance
“…Therefore, surface functional groups and chemical compositions of MXenes, which influence their electrical properties, are capable to impact their optical properties. The DFT calculations predicted that pristine MXenes, which are not having surface terminal groups, exhibit metallic behavior due to the overlapping of conduction and valence bands at the Fermi level . However, the outermost metal layers of MXene are inevitably terminated with surface terminal groups during their synthesis, and DFT calculations predicted that electronic structure of MXenes is sensitive to the type and orientation (relative to the MXene sheet) of surface terminations. ,,, G. R. Berdiyorov employed DFT calculations to divulge the role of surface terminations on optical properties of Ti 3 C 2 T 2 (T = −F, −O, −OH) MXene . The results concluded that all surface terminations result in higher absorption and reflectivity for Ti 3 C 2 T 2 MXene in the UV range as compared to pristine MXene .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Therefore, surface functional groups and chemical compositions of MXenes, which influence their electrical properties, are capable to impact their optical properties. The DFT calculations predicted that pristine MXenes, which are not having surface terminal groups, exhibit metallic behavior due to the overlapping of conduction and valence bands at the Fermi level . However, the outermost metal layers of MXene are inevitably terminated with surface terminal groups during their synthesis, and DFT calculations predicted that electronic structure of MXenes is sensitive to the type and orientation (relative to the MXene sheet) of surface terminations. ,,, G. R. Berdiyorov employed DFT calculations to divulge the role of surface terminations on optical properties of Ti 3 C 2 T 2 (T = −F, −O, −OH) MXene . The results concluded that all surface terminations result in higher absorption and reflectivity for Ti 3 C 2 T 2 MXene in the UV range as compared to pristine MXene .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…(a) Different elements that can be used to build MXenes as shown by different colors . (b) Schematic illustration of various types of MXenes . (c) Atomic arrangement and chemical composition of various MXenes reported in the literature …”
Section: Fundamentals Characteristics and Advances In Ti3c2 Mxenesmentioning
confidence: 99%
“…[ 185,186 ] The commercial production of NH 3 is dominated by the Haber‐Bosch process, but it involves high temperature (400–500 °C) and pressure (200–250 bar), leading to high production cost and safety hazard. [ 187 ] Photocatalytic nitrogen reduction is the more attractive option for ammonia production compared to the Haber–Bosch process, because the photocatalytic reduction of N 2 into NH 3 is achieved at room temperature and pressure. [ 188–190 ] The key factor of photocatalytic nitrogen reduction is to reduce the recombination of photoinduced electrons and holes, producing more photoinduced electrons to participate in nitrogen reduction.…”
Section: Applications Of Metal Carbide Cocatalystsmentioning
confidence: 99%